Penerapan Model Problem Based Learning (PBL) dalam Proses Belajar pada Pembelajaran Tematik Terpadu di Kelas IV SDN 29 Rantau Batu Pasar Punggasan Pessisir Selatan - Sutrada, Erik; Sukma, Elfia (Universitas Negeri Padang, 2022)
This study aims to obtain a description of the implementation of the Problem Based Learning Model by the teacher in the learning process of the fourth grade students of SDN 29 Rantau Batu Pasar as seen from the PBL learning steps used by the teacher in the teaching and learning process, the obstacles in the implementation of the Problem Based Learning model. and the efforts made to overcome the obstacles in the Problem Based Learning model in the student learning process. This research is a descriptive study with a qualitative approach. The research subjects were fourth grade teachers and fourth grade students of SDN 29 Rantau Batu Pasar. Data collection techniques include observation, interviews and documentation. The analysis technique used in this research is a descriptive analysis model consisting of data collection, data organizing, data management, verification and interpretation of data, conclusions. Based on the results of the research that has been done, the results show that the Problem Based Learning Model is very effective. used in an integrated thematic learning process where the PBL Model is a learning model that involves students directly in solving problems and can solve the problems faced according to their knowledge and accompanied by logical reasons. And it is supported by several relevant studies which show that this PBL model is effective in an integrated thematic learning process.